2003
DOI: 10.1080/00071660310001618334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat stress on oxidative stress, lipid peroxidation and some stress parameters in broilers

Abstract: 1. This study was conducted to determine the effects of heat stress on fearfulness, leucocyte components, oxidative stress and lipid peroxidation in two commercial broiler strains, Cobb (C) and Ross (R). 2. At 36 and 37 d of age birds were exposed to 38 +/- 1 degree C for 3 h. Rectal temperatures, duration of tonic immobility (TI), haematocrit values, proportions of leucocyte components (heterophil, lymphocyte, basophil, eosinophil, monocyte), malondialdehyde (MDA) concentrations and antioxidant enzyme activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
289
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(323 citation statements)
references
References 39 publications
23
289
3
8
Order By: Relevance
“…Similar observations were made in broilers (Merlet et al 2005). The literature reports strain differences in response to free-ranging behaviour (Nielsen et al 2003), heat stress (Altan et al 2003) and BW (Nthimo et al 2004) in chickens. In this study, we anticipated strain differences in foraging behaviour under heat stress conditions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar observations were made in broilers (Merlet et al 2005). The literature reports strain differences in response to free-ranging behaviour (Nielsen et al 2003), heat stress (Altan et al 2003) and BW (Nthimo et al 2004) in chickens. In this study, we anticipated strain differences in foraging behaviour under heat stress conditions.…”
Section: Discussionsupporting
confidence: 72%
“…The literature shows that there are strain differences in response to heat stress and that slower growing strains range more widely (Altan et al 2003;Nielsen et al 2003) compared to fast-growing birds. Even among slow-growing strains, thermoregulatory capabilities vary.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies demonstrated that heat stress induces oxidative stress in the body [4,5,6]. It has been demonstrated that heat stress is one of the most important stressors in the hot regions of the world (Altan, 2003).It results the generation of free radicals and other reactive oxygen species(ROS) (Chihuailaf et al, 2002) which leads to cellular and tissue damage (Tkaczyk andVizek, 2007). Free radicals and ROS have been demonstrated to have adverse effects on erythrocytes [7,8,9,10].Oxidative stress has been implicated with increased protein degradation through several mechanisms, including the activation of proteases and increasing the expression of genes involved in autophagy and proteolysis [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that heat stress is one of the most important stressors in the hot regions of the world (Altan, 2003).It results the generation of free radicals and other reactive oxygen species(ROS) (Chihuailaf et al, 2002) which leads to cellular and tissue damage (Tkaczyk andVizek, 2007). Free radicals and ROS have been demonstrated to have adverse effects on erythrocytes [7,8,9,10].Oxidative stress has been implicated with increased protein degradation through several mechanisms, including the activation of proteases and increasing the expression of genes involved in autophagy and proteolysis [11,12,13]. ROS have been shown to impair protein synthesis by preventing mRNA translation [14,15,16,17,18].Acute heat-stressed broiler chickens had a 2-fold increase in malondialdehyde, a marker of lipid peroxidation, in skeletal muscle [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que estressores ambientais, nutricionais, físicos, sociais ou fisiológicos estão envolvidos com o bem estar e o desenvolvimento animal (ALTAN et al, 2003). Neste sentido, o estresse provocado pelo excesso de calor é um dos maiores responsáveis por perdas na criação intensiva de frangos de corte, principalmente quando ocorre próximo ao momento do abate (FURLAN, 2006).…”
Section: Estresse Térmico E Resposta Imune Em Avesunclassified